The community planning handbook : how people can shape their cities, towns and villages in any part of the world - Wates, Nick (New York, NY : Routledge, 2014)
'Growing numbers of residents are getting involved with professionals in shaping their local environment, and there is now a powerful menu of tools available, from design workshops to electronic maps. The Community Planning Handbook is the essential starting point for all those involved: planners and local authorities, architects and other practitioners, community workers, students and local residents. It features an accessible how-to-do-it style, best practice information on effective methods, and international scope and relevance. Tips, checklists and sample documents help readers to get started quickly, learn from others' experience and to select the approach best suited to their situation. The glossary, bibliography and contact details provide quick access to further information and support. This fully updated new edition contains extra material on following up after community engagement activities'--
'Description Growing numbers of residents are getting involved with professionals in shaping their local environment, and there is now a powerful menu of tools available, from design workshops to electronic maps. The Community Planning Handbook is the essential starting point for all those involved: planners and local authorities, architects and other practitioners, community workers, students and local residents. It features an accessible how-to-do-it style, best practice information on effective methods, and international scope and relevance. Tips, checklists and sample documents help readers to get started quickly, learn from others' experience and to select the approach best suited to their situation. The glossary, bibliography and contact details provide quick access to further information and support. This fully updated new edition contains extra material on following up after community engagement activities'--
Includes bibliographical references and index.
Keywords: Community development -- Planning -- Handbooks, manuals, etc; Planning -- Citizen participation -- Handbooks, manuals, etc